Indicador do eco-conhecimento: desenvolvimento sustentável sob a ótica acadêmica - Alves, Charmenie Santana (2009)
In the face of contemporary issues (social, economic, environmental) for the premises of sustainable development, this project seeks to scrutinize what is the Federal University of Uberlandia s position on those issues aimed at promoting a sustainability Eco-Knowledge indicator to interpret the perception of the academic community related to the topic. With this purpose we could see through a descriptive analysis / deductive explanation that the issues facing sustainable development are not studied in depth at the University, apart from some academic units, and because of that the graduates have diffuse and inchoate knowledge acquired a greater percentage in the media, television, newspaper, magazines and internet. This result is reinforced when we compare the indicators of Eco-Knowledge in Natural Perspective (2.94) and Social Perspective (2.03), developed using data obtained by the survey, with an ideal value stipulated arbitrarily (6.3 ). For the fostering of these indicators are considered seven components that comprise the Natural Outlook, and also seven components that illustrate the Social Perspective which is made up of the Conceptions (1), Actions(2), Importance (3), Impediments (4), Consumerism (5), Professional Field (6), Source of Knowledge-UFU (7) related to the concept and the promotion of sustainable development for both the natural environment issues which are related to the preservation of natural resources, and to the social context which issues include paradigms and behaviors of contemporary society. From these results it is noticeable that the difficulties regarding the implementation and fostering of sustainable development in the spheres of production of scientific knowledge, goes beyond the issues related to fragmentation of knowledge and the need for a global vision linked to different levels of ideological reality. The problem is the lack of approach of this theme forward all courses that make up the academic sphere, that is, studies addressed to Sustainable Development are restricted to small groups interested in sustainability on the subject.